Coherent and Polarization Optics (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Coherence and polarization are two of the intrinsic properties of a light field, which play a crucial role in determining the light beam propagation and light–matter interaction. The manipulation of coherence and polarization was recognized as an available method to produce many peculiar physical phenomena, which can be superior in some of these applications, such as free-space optical communications, microdensitometry, optical information processing, and plasmonics. The aim of this reprint is to provide a comprehensive exploration of manipulation of coherence and polarization of light and applications.